EDUCATIONAL TECHNOLOGIES AND SOCIO-EMOTIONAL COMPETENCIES IN LEGAL EDUCATION: PATHS TOWARD A HUMAN-CENTERED LAW CURRICULUM - de Amorim, Dandara Christine Alves (Seven Editora, 2025)
This article aims to investigate how educational technologies can contribute to the development of socio-emotional competencies in legal education, with an emphasis on the formation of professionals who are more humane, critical, and socially engaged. It is a qualitative, exploratory study based on bibliographic and documentary research. The analysis undertaken considers the relevance of competencies such as empathy, active listening, collaboration, ethical argumentation, and emotional self-regulation, which are understood as essential to the practice of law in contemporary society. It is observed that active methodologies mediated by technology — including virtual learning environments, thematic forums, simulations, podcasts, and mediation practices — foster student protagonism, meaningful learning, and the humanization of educational processes. Based on this observation, a hybrid pedagogical model with a socio-emotional focus is proposed, integrating theory, practice, and affective experience within the context of legal education. The articulation between educational technologies and the human dimension of legal training emerges as a promising path for pedagogical innovation in higher education. However, such integration requires structured institutional planning, ongoing investment in teacher training, and a commitment from institutions to pedagogical projects that intentionally and critically promote the integral development of students.DOI: https://doi.org/10.56238/sevened2025.040-001